IMPLEMENTASI PENDIDIKAN AGAMA DAN KEAGAMAAN PASCA KONFLIK DI PAPUA - Mujizatullah Mujizatullah (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This research aims to describe the implication of social conflict to educationof religion (formal and informal) implementation. This was conductedat Abepura, Papua. Data was collected by depth interview andobservation.In Papua, conflict was caused by ethnical problem and social distancebetween local and comer. This conflict relatively didn't influence learningactivity. Local government always give more attention to school inPapua